2020
DOI: 10.1002/er.5981
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrolyte thickness manipulation on enhancing carbon deposition resistance of methane‐fueled solid oxide fuel cell

Abstract: Summary Dual‐layer hollow fiber (DLHF) micro‐tubular solid oxide fuel cell (MT‐SOFC) consisting of nickel oxide‐yttria‐stabilized zirconia (NiO‐YSZ) anode/YSZ electrolyte was fabricated via a single‐step phase inversion‐based co‐extrusion/co‐sintering technique in order to investigate the effect of different electrolyte extrusion rates (1‐5 mL min−1) at different sintering temperature (1350°C, 1400°C, and 1450°C) under methane (CH4) condition. The DLHF co‐sintered at 1450°C was chosen as optimum temperature du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The low peaks were resulted from the very low content of Cu used. Furthermore, the Cu thickness of 1.36 μm in Cycle 5 was considerably thin compared to the thickness of a typical anode in MT‐SOFC which was 150 μm 28 …”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The low peaks were resulted from the very low content of Cu used. Furthermore, the Cu thickness of 1.36 μm in Cycle 5 was considerably thin compared to the thickness of a typical anode in MT‐SOFC which was 150 μm 28 …”
Section: Resultsmentioning
confidence: 94%
“…The reduction transition in permeability signifies pore blockage which possibly occurred during deposition of Cu. As shown in, 28 MT-SOFC made via phase inversion was known to induce several types of porosity, ranging from nano-size sponge-like porosity to micron size finger-like projections. 18 Based on Figure 4, the 140 nm size Cu grain might have blocked smaller pores, thus greatly reducing the gas flow.…”
Section: Copper Layer Formation and Effect On Conductivity And Gas Pe...mentioning
confidence: 97%
See 1 more Smart Citation
“…Many studies have shown that the thickness of the electrolyte attaches tightly to the ohmic impedance. The ohmic resistance can be reduced by adopting a thinner electrolyte 16‐18 . But the excessive reduction of electrolyte thickness will result in a significant decrease in its intensity.…”
Section: Introductionmentioning
confidence: 99%
“…The ohmic resistance can be reduced by adopting a thinner electrolyte. [16][17][18] But the excessive reduction of electrolyte thickness will result in a significant decrease in its intensity. The polarization resistance of SOFC will increase dramatically when the operating temperature decreases.…”
Section: Introductionmentioning
confidence: 99%